ANALISIS BIAYA PRODUKSI DALAM MENINGKATKAN OMZET PENJUALAN PADA USAHA BAKERI MEREK DAGANG RR RUMAH ROTI - Yeri, Engel Bertus; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study is titled "Analysis of Production Costs in Increasing Sales Revenue at RR Rumah Roti Bakery Business Brand." The general problem addressed in this research is: How does the calculation of production costs contribute to increasing sales revenue, with the following sub-problems: (1) How is the Calculation of Production Costs at RR Rumah Roti Bakery Business implemented to increase sales revenue? (2) How is the Application of Full Costing Method in Increasing Sales Revenue at RR Rumah Roti Bakery Business? The aim of this study is to understand how the Calculation and application of the Full Costing Production Cost method contribute to increasing sales revenue at RR Rumah Roti Bakery Business. The research approach used is qualitative with a descriptive research method. Data collection techniques involve interviews and documentary studies. Data collection tools include interview guides, field notes, and a camera. The results of this research indicate that: (1) Regarding the calculation of production costs at RR Rumah Roti Bakery Business, it is evident that the selection of the Variable Costing method is more suitable for the business's circumstances. This method allows a focus on costs directly related to bread production at RR Rumah Roti Bakery, providing a better understanding of each product's contribution to fixed costs and profits. However, the choice of cost method will impact financial reporting and overall company performance analysis. (2) The implementation of the Full Costing method at RR Rumah Roti Bakery Business assists in enhancing the accuracy of production cost calculations. By incorporating all cost components, including fixed and variable factory overhead costs at RR Rumah Roti Bakery, the company can calculate total production costs more accurately